Pengaruh Label Halal, Kualitas Produk, dan Harga Terhadap Volume Penjualan dengan Digital Marketing Sebagai Variabel pada Industri Kecil Kuliner di Ponorogo - Mochammad Syahrul Utomo Syam; Luhur Prasetiyo; Shinta Maharani (Journal of Economics, Law, and Humanities, 2025)
This study aims to analyze the influence of halal labels, product quality, and price on sales volume in small culinary industries in Ponorogo, considering digital marketing as a moderating variable. The research uses a quantitative approach with a descriptive research type. Primary data was obtained from 100 respondents selected using probability sampling with stratified random sampling based on Slovin's formula. Data collection was conducted through questionnaires, and data analysis involved validity tests, reliability tests, classical assumption tests, T-tests, F-tests, coefficient of determination (R²), and Moderated Regression Analysis (MRA) using SPSS 16. The results show that the halal label significantly influences sales volume by 23.9%, product quality has an insignificant influence of 11.2%, and price has a significant influence of 22.5%. Simultaneously, the three variables influence sales volume by 27.9%. Digital marketing is proven to moderate the relationship, strengthening the effect of the halal label by 43.6%, weakening the effect of product quality by 43%, and strengthening the impact of price by 44.7%. Simultaneously, digital marketing influences sales volume by 57.2%. Thus, digital marketing effectively enhances the influence of halal labels and prices on sales volume in Ponorogo’s small culinary industries.